Achieving excellence in fundraising - Tempel, Eugene R., 1947-; Seiler, Timothy L., 1946-; Aldrich, Eva E., 1963-; Rosso, Henry A., 1917-; Maehara, Paulette (Essential texts for nonprofit and public leadership and management, 2011)
"Hank Rosso's Achieving Excellence in Fund Raising, 3rd Edition, explains the fund raising profession's major principles, concepts and techniques. A host of respected authors demonstrate why fund raising is a strategic management discipline, and elucidate each step in the fund raising cycle: assessing human and societal needs, setting goals, selecting gift markets and fund raising techniques, soliciting new gifts, and encouraging renewals. This book provides a conceptual foundation for the fund raising profession, thoroughly examining its principles, strategies and methods. Using practical examples, the authors explain the reasoning behind the planning and selection of strategies for all fund raising activities. Edited by Gene Tempel, Executive Director of Indiana University's Center on Philanthropy, this third edition of the Rosso's fund raising classic both retains the original philosophical principles of the first edition and offers new insights on recent fund raising developments. Each chapter has been updated, and Tempel has added new sections on technology and fund raising, the internet, women as donors, stewardship, and fund raising as a profession. Authors include such fund raising luminaries as Tim Seiler, Dwight Burlingame, Lilya Wagner, Mal Warwick, Kay Sprinkel Grace and Kim Klein."--